Adopt-a-Robot: A Story of Attachment (Or the Lack Thereof) - Herath, D.; Kroos, Christian; Stevens, C.; Burnham, D. (Institute of Electr ical and Electronics Engineers, Inc., 2013)
Robots have diffidently started to invade human spaces, but are still limited to very rudimentary forms such as robot vacuum cleaners and various entertainment platforms. Dramatic changes with respect to the number of robots in homes and offices, however, can be foreseen for the near future as sensing, computing and associated technologies mature. Currently, it is not known how we humans will treat machine companions when they will be with us over prolonged periods of time and share our personal space. In this exploratory study we investigated whether participants would form a bond with a small, basic research robot in an adoption scenario whereby the robot's initial interaction abilities were upgraded in two steps. We were particularly interested in investigating whether any increases in attachment would be related to the 2 steps of progressively heightened technical sophistication of the robot over a prolonged (six month) period of time.